Characteristics of Roasted Meltique Buffalo Meat Marinated with Papaya Extract - Yudhistira, Mohammad Ariq; Apriantini, Astari; Wulandari, Zakiah (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
Buffalo meat is recognized for its high nutritional value, low fat content, and elevated calcium levels, though its tough texture can limit consumer acceptance. To address this, meltique processing by injecting fat emulsions into muscle tissue, was applied using various animal and vegetable fats (beef tallow, Wagyu tallow, coconut oil, and palm oil) combined with papain enzyme to enhance tenderness and flavor. The aim of this study was to evaluate physicochemical characteristics of meltique buffalo meat injected with different fat emulsions. This study used a completely randomized design (CRD) with five treatments and three replications. The experiment consisted of five treatments: roasted buffalo meat as control, and samples marinated with papaya extract then injected with commercial beef tallow (T1), Wagyu beef tallow (T2), coconut oil (T3), and palm oil (T4). Moreover, all those samples were grilled and analyzed for chemical contents such as moisture, ash, protein, fat  and carbohydrat content and also physic properties such as marbling grade, fat and meat color, pH and cooking shrinkage. All treatments significantly increased moisture, fat, and marbling scores (p < 0.05) compared to control, with coconut oil injection yielding the highest fat content and marbling scores. Physical characteristics such as pH, tenderness, and cooking loss remained within acceptable quality ranges. This study concludes that combining papain and fat emulsions effectively enhances buffalo meat's tenderness, physical and nutritional quality, with coconut oil treatment showing the most favorable results.